Actors and institutions in the Brazilian Climate Change Policy (Sustainability in Debate, 2018)
This research observed that all Brazilian institutions for climate change policy adopted the same governance model, characterized by three common factors: (1) institutional diversity, (2) cooperation and (3) political competition. An analysis of the Inter-Ministerial Commission on Global Climate Change (CIMMGC in Portuguese) was realized. The idea was to assess the effects of a bigger institutional diversity on cooperation and political competition among actors involved in the institution mentioned above. Some elements, such as the elevated inclusiveness of political actors and the accountability reinforcement in the political decision-making process are essential to this Case Study. The outcome of this analysis pointed out that no democratic governance absence could result from a bigger political inclusiveness in the decision-making process of the Brazilian climate change policy. The Inter-Ministerial Commission on Global Climate Change (ICGCC) did not lose its institutional dynamism and decision-making authority on goals delegated by the Brazilian National Plan on Climate Change, despite the reinforcement of accountability mechanisms in political process.